2005
DOI: 10.1073/pnas.0504869102
|View full text |Cite
|
Sign up to set email alerts
|

False beliefs about fattening foods can have healthy consequences

Abstract: We suggested to 228 subjects in two experiments that, as children, they had had negative experiences with a fattening food. An additional 107 subjects received no such suggestion and served as controls. In Experiment 1, a minority of subjects came to believe that they had felt ill after eating strawberry ice cream as children, and these subjects were more likely to indicate not wanting to eat strawberry ice cream now. In contrast, we were unable to obtain these effects when the critical item was a more commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 19 publications
(14 reference statements)
3
73
0
Order By: Relevance
“…Visual inspection in Table 3 of the mean increased belief ratings before and after false feedback indicates a very consistent advantage for this condition over the control condition. However, like in the imagination inflation studies, analyses of ‘Believers’ indicate that it was usually the minority of study participants who showed clear evidence of responding positively to the intervention (range 18%, in Bernstein et al, 2005a, Study 1, to 53%, in Laney, Morris, Bernstein, Wakefield, & Loftus, 2008, Study 2).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Visual inspection in Table 3 of the mean increased belief ratings before and after false feedback indicates a very consistent advantage for this condition over the control condition. However, like in the imagination inflation studies, analyses of ‘Believers’ indicate that it was usually the minority of study participants who showed clear evidence of responding positively to the intervention (range 18%, in Bernstein et al, 2005a, Study 1, to 53%, in Laney, Morris, Bernstein, Wakefield, & Loftus, 2008, Study 2).…”
Section: Resultsmentioning
confidence: 96%
“…Typically ‘Believers’ reported an increase on the autobiographical belief scale that ranged from 1 to 2 points, remaining below the scale midpoint, for an event at a theme park (Berkowitz, Laney, Morris, Garry, & Loftus, 2008) to 3–5 points, increasing beyond the scale midpoint, for food‐related events (D. M. Bernstein et al, 2005a, 2005b; Laney et al, 2008; Laney et al, 2008; Scoboria, Mazzoni, Jarry, & Bernstein, 2012). In some cases, belief ratings recorded by ‘Believers’ after false feedback were as high as 6.48 on the 8‐point scale (Laney et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations